2014
DOI: 10.1159/000366197
|View full text |Cite
|
Sign up to set email alerts
|

Repigmentation of Extensive Inflammatory Vitiligo with Raised Borders Using Early and Aggressive Treatment

Abstract: Inflammatory vitiligo with raised borders (IVRB) is a rare subtype of vitiligo described as having a rim of raised erythema at the periphery of the depigmented patches. The etiology is poorly understood, and there are few reports of successful treatment of the condition in the literature. We report a 38-year-old South Asian male who presented with diffuse depigmented macules and patches surrounded by blue-gray rims involving a large body surface area. Light microscopy revealed inflammatory vitiligo. He was tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In case of KP, it has been suggested that this sign preludes the development to mixed vitiligo, which also supports the theory that segmental and non‐segmental vitiligo may reflect different variants on a single disease spectrum . The effect of skin manifestations on treatment response was not assessed in this systematic review, although some suggested that the presence of inflammatory vitiligo with raised borders should be tackled with early and aggressive treatment …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of KP, it has been suggested that this sign preludes the development to mixed vitiligo, which also supports the theory that segmental and non‐segmental vitiligo may reflect different variants on a single disease spectrum . The effect of skin manifestations on treatment response was not assessed in this systematic review, although some suggested that the presence of inflammatory vitiligo with raised borders should be tackled with early and aggressive treatment …”
Section: Discussionmentioning
confidence: 99%
“…47 The effect of skin manifestations on treatment response was not assessed in this systematic review, although some suggested that the presence of inflammatory vitiligo with raised borders should be tackled with early and aggressive treatment. 48 The reported prevalence of the different skin manifestations varied, as well as the association with disease activity, suggesting different definitions and assessment methods of these clinical signs in the different studies. This was also reflected in the heterogeneity parameter of the meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the fact that late treatment would deprive the patients of chances for complete repigmentation. [11][12][13][14]17 Fortunate enough, successful repigmentation as defined by Gan et al 19 was achieved in all patients in a mean duration of 6.88 months.…”
Section: Discussionmentioning
confidence: 73%
“…In the current study, we considered a single vitiligo patch as an “emergency” situation opting for better response aiming at lower incidence of recurrence even in resistant cases as acral and segmental vitiligo. This is supported by the fact that late treatment would deprive the patients of chances for complete repigmentation 11–14,17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation